Laïcité à l'école : évolution du concept dans une approche historique et juridique - Céline Chauvigné
This article applies to reconstruct the political social processes that allow the definition of secularism in schools. To do this, we conducted a historical study, by relying on a legal, political and social reality, which attempts to show the tensions involved and evolution of educational and teaching models relating thereto. Through the question of religious symbols, we will seek to identify the history of conceptions of secularism from 1905 to 2016. This cartography is the result of a complex history linking social, political and geopolitical data with repercussions on life of schools.